Memory and trauma in international relations : theories, cases and debates - Resende, Erica Simone Almeida; Budryte, Dovile (New York, NY : Routledge, 2014)
"This work seeks to provide a comprehensive and accessible survey of the international dimension of trauma and memory and its manifestations in various cultural contexts"--
part I. Theoregical approaches and debates -- part II. Cases.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: International relations -- Social aspects; Psychic trauma; Collective memory; Electronic books